NEW LANDSLIDES ON SOUTH-WESTERN CRIMEAN SEACOAST: RISK ASSESSMENT AND LANDSLIDE CONTROL TECHNIQUES - Boyko, K. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Geologic and engineering development of the South Coast of the Crimea, which remains an active geodynamic and tectonic structure, has always been uneasy task due to numerous exogenous geological processes (EGP), with landslides being most dangerous and abundant in the region. Over half a century steps have been taken to stabilize slopes and to reveal major landsliding factors. There have also been suggested a number of geotechnical surveys, enabling to forecast and detect early landsliding. Although buttresses have been consolidated and great landsliding systems stabilized, there, still, tend to appear new shallow erosive and anthropogenic landslides in the shallow illuvial-deluvial sediments that cover the Middle Jurassic and Tauriс flysch formations. Abundant small shallow landslides are not easy to be detected visually. Based on probability theory, there have been developed spatial modelling methods for landslide-prone areas, such as geodynamic or landslide potential methods, though they still require refining by processing detailed information from large-scale surveys. On the other hand, calculating coefficients of linear and areal affection for the areas prone to landsliding does not reveal either dynamics or directions of the process. Thus, there arises a need to devise an upgraded method of spatial evaluating regional landslides, based on informative and reliable values, to assess risks of new landslides activation and formation. The study uses an approach that allows for estimating risks of new landslides extension, with both an activity (the dynamics) of landslides within the region, and the intensity of their extension (spatial affection) in consideration. For the first time based on the Zolotarev historic and geolodical method, there is given the quantitative assessment for different genetic types of the adjacent strata, to confirm the risk of distribution rate within the South-Western Crimean Seacoast. Based on the research findings, there is build a map of shallow landslide risk distribution. The implemented model illustrates both the direction of landslide extension, and geological environment alterations. When compiling a map of landslide risk distribution combined with a map of anthropogenic impact distribution, there can be laid a foundation for territory zoning based on both geological environment sustainability to technogenic impacts and shallow landslides occurrence.